Is there a role for the IGF system and epidermal growth factor (EGF) in the pathogenesis of adrenocortical adenomas? A preliminary case-control study - Lazúrová, I; Jochmanová, I; Sotak, Š; Špaková, I; Mareková, M (Physiological research, 2020)
Adrenal incidentalomas (AI) are very common and mostly they are non-functioning adenomas (NFA). NFAs are often associated with insulin resistance and metabolic syndrome. Several biomarkers, including certain growth factors, may participatein the pathogenesis ofmetabolic changes in patients with adrenal adenomas.Patients with NFA and age-matched control subjects were enrolled in the study. Data on age, gender, presence of metabolic syndrome or its components were obtained for each subject. Blood samples were obtained and glycemia, insulinemia, lipid profile, and selected growth factor levels were measured. Forty-three patients with NFA and 40 controls were included in the study. Differences were not found in the metabolic syndrome and its components prevalence or in the biochemical profile between patients and the control group. Significant differences were noticed in the levels of IGF1, IGF2, and IGFBP3 (p=0.016, p=0.005, p=0.004, respectively), but there were no differences in VEGF or EGF concentrations. In NFA patients, an association between glycemia and EGF levels was present (p=0.026). No significant correlations between tumor size and insulin or growth factor concentrations were present in AI patients. Significantly higher serum IGF1, IGF2, and IGFBP3 concentrations in NFA patients may support the role of the IGF axis in the pathogenesis of adrenocortical lesions.No correlation between IGFs or IGFBP3 and parameters of glucose or lipid metabolism was found. Present results may support the role of the growth hormone axis rather than hyperinsulinemia and insulin resistance in the pathogenesis of adrenocortical adenomas.
Keywords: senioři; Insulin-Like Growth Factor I; adrenokortikální nádory; senioři nad 80 let; Male; Prognosis; epidermální růstový faktor; Middle Aged; mužské pohlaví; studie případů a kontrol; Adrenal Cortex Neoplasms; Adult; Insulin-Like Growth Factor II; Biomarkers, Tumor; insulinu podobný růstový faktor II; Aged, 80 and over; ženské pohlaví; nádorové biomarkery; prognóza; Adrenocortical Adenoma; Humans; Insulin-Like Growth Factor Binding Protein 3; Epidermal Growth Factor; IGFBP-3; lidé středního věku; dospělí; Female; Aged; adenom kůry nadledvin; lidé; Case-Control Studies; insulinu podobný růstový faktor I